Scoping Review: Efektivitas Vasopresor terhadap Hipotensi Intraoperatif - Sari Asyira Vianita Ohorella; Adelya Putri Aisyah; Rezky Aulia Putri; Asya Qoblianingtyas; Safrian Safrian; Ratih Kusuma Dewi (PPNI UNIMMAN, 2025)
Intraoperative hypotension, particularly during spinal anesthesia in cesarean sections or major surgeries, is a common complication that can adversely affect maternal hemodynamics and organ perfusion, including fetal circulation. Vasopressors such as norepinephrine, phenylephrine, and ephedrine are widely used to manage this condition. This study employed a scoping review, defined as a type of research synthesis aimed at mapping the literature on a specific topic or field, providing an opportunity to identify key concepts, research gaps, and types and sources of evidence to inform clinical practice, policy-making, and further research. A systematic search was conducted across 10 recent experimental and clinical studies evaluating the effectiveness and safety of vasopressors in adult patients, particularly ASA I–II parturients, during surgical procedures. The results indicate that norepinephrine tends to maintain blood pressure with a lower incidence of tachycardia compared to ephedrine, while phenylephrine effectively prevents systemic vascular resistance decline but may reduce heart rate and cardiac output in a dose-dependent manner. Effects on fetal cerebral perfusion and cerebral oxygenation were generally similar across vasopressors. No significant differences were observed in neonatal Apgar scores or maternal complications. In conclusion, norepinephrine and phenylephrine are effective alternatives for managing intraoperative hypotension, whereas ephedrine increases cardiac output but may elevate the risk of tachycardia. Selecting the appropriate vasopressor is crucial to ensure maternal and neonatal safety.